Effect of Drip Irrigation Scheduling on Yield of Rose Grown in Greenhouse - Hasan, M; Singh, D K; Sirohi, N.P.S; Sarangi, A; Singh, A K (Journal of Agricultural Engineering, 2008)
Irrigation scheduling inside climate control greenhouse is important parameter for the appropriate design and successful operation and management of drip irrigation system. It directly affects the quality and quantity of crop production system inside climate control greenhouse. Experiments were carried out for irrigation scheduling of cut flower rose (c.v First Red) grown inside climate controlled greenhouse with three treatments 100%, 80% and 60% ETc and three replications. The study involved design and installation of drip irrigation system inside climate control greenhouse, field observation and sampling, analysis of soil, water and plant and determination of irrigation scheduling of rose crop grown under climate control greenhouse. Irrigation scheduling directly affected the cut flower yield of rose grown in climate controlled greenhouse. The maximum yield per plant was found to be 48 cut flowers per plant in the year 2004 with total amount of irrigation as 112 liter per plant and irrigation scheduling done with 100% ET. The yield per plant was found to be highest for T1 which corresponds to 100% ET. The yield gradually increased from the year 2000 to year 2005 in all the treatments and this effect was more prominent for T1. The year 2004 was supposed to be the fully matured or saturating level for the rose plant as after that the yield started decreasing for all the treatments.